SEX AND LEFT HEART ULTRASOUND DATA DURING ATRIAL FLUTTER - YabluchanskayaТ.P.; Vakulenko, I.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
There has been studied gender features of heart biomechanics during atrial flutter (research group - AF) in comparison with sinus rhythm (comparing group - SR). The research group consisted of 41 patients with constant AF, 19 females and 22 males, average age was 62±15. The group of comparing consisted of В 29 patients with sinus rhythm, 14 females and 15 males, average age was 65±11. Echocardiographic analysis has been carried out taking into account left ventricle (LV), left atrium (LA) and aorta biomechanic and geomyetry indices in 10 consistant heart cycles. In each heart cycle there has been measured and calculated endsystolic and enddyastolic sizes and volumes of LV, endsystolic and enddyastolic thickness of interventricular septum and LV backwall, LV stroke volume and ejection fraction (EF), LA and aorta linear dimension. Each group of patients has been devided into subgroups according to their gender. The results statistical calculation realized using Exel programme. Acording to all of the indices there has been calculated average (М), maximal (max) and minimal (min), moda (moda) and excess (ex) values. Distinction reliability of indices between groups of patients with AF and SR has been determined using Student method. Obtained gender distinctions in theLVindices more refered to indices absolute values, but not to the distribution law. Similar standard deviations and excess values in the subgroups of comparing patient groups with AF and SR are the reason for the same ultrasound research approach of males and females. In spite of chaotic character of heart biomechanic cycle changes in the subgroups of male and female patients, studied geometric and biomechanical indices, excluding LA dimensions, during AF are corresponding the indices during SR.